The pattern of learned visual improvements in adult amblyopia - Astle, Andrew T.; Webb, Ben S.; McGraw, Paul V. (Association for Research in Vision and Ophthalmology (ARVO), 2011)
Purpose. Although amblyopia is diagnosed in terms of a monocular letter acuity loss, individuals typically present with deficits on a wide range of spatial tasks. Many of these deficits can be collapsed along two basic visual dimensions (visual acuity and contrast sensitivity) that together account for most of the variability in performance of the amblyopic visual system. In this study, this space was exploited, to target the main deficits and fully characterize the pattern of learned visual improvements in adult amblyopic subjects.